Algerian Multilingualism among First-year Master Students in Constantine 1 English Department as an Example of Language Contact Context (مجلة الواحات للبحوث والدراسات, 2025)
For  the  sake  of  knowing  the  causes  and  results  of  language  contact an rivalry in Algeria, this  paper is  interested  in  the  development  and  the contact  of  Berber, Arabic, French and English. In addition, it focuses on   how  these languages  influence  one  another  and  cause  changes  on  each  other in one of the academic contexts. It also focuses  on  the different  mechanisms  of  language  change.   For that, an observational evaluation of the developmental stages in the teaching of translation for first-year Master students of English is used as a method because translation is the best area where different languages meet and influence one another. As a result, multitude of languages are used among the chosen population. Although the use of these languages is different from one student to another, they meet in one spot, which is the translation process.Keywords: Language contact, multilingualism, Algeria, translation, First year Master students.